BURNOUT SYNDROME AS A MANIFESTATION OF TEACHER’S PROFESSIONAL DEFORMATION - Дубчак, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
Professional deformation is the destruction that occurs during work activity and negatively affects its performance. In addition, the destructions generate professionally undesirable qualities changing both professional and personal behaviour. Furthermore, professional deformation has the greatest impact on the personal characteristics of representatives of those professions whose work relates to people (teachers, psychologists, social and medical workers, officials, leaders, police officers, etc.). One of the significant signs related to professional deformation of teachers is the emotional burnout syndrome. Burnout syndrome is viewed as a process of gradual loss of emotional, cognitive and physical energy, which is characterized by the symptoms of emotional and mental exhaustion, as well as physical fatigue, personal isolation, depersonalization, and reduced satisfaction in performance. It is mainly regarded as the result of stress which has not been successfully dealt with at the workplace. Above all, there are three main symptoms of emotional burnout syndrome: extreme exhaustion, detachment from clients (patients, pupils, students) and from work, a sense of inefficiency and lack of achieving high-performance goals. Recent research suggests five key groups of symptoms regarding burnout syndrome. These include both physical, emotional, behavioural, social symptoms and intellectual state. As a result, scientists came to the conclusion that personal, role and organizational factors play an essential role in professional burnout. This paper gives an overview of diagnostic criteria and methods of prevention for burnout syndrome, which are of primary importance for representatives of all professions, especially those who are at risk.